CONSUMER PREFERENCE FACTORS THAT AFFECT BUYING INTEREST IN JAIL COFFEE KEMAYORAN - Martin Caniago Putra Dewa; Hari Iskandar (ZILLZELL MEDIA PRIMA, 2024)
The coffee industry is one of the popular industries and is also very closely related to the people of Indonesia. The development of high and increasing production and consumption of coffee and it’s processing today is also inseparable from the phenomenon that occurs in the community. The creation of a trend in consuming coffee has now made coffee a lifestyle in the social environment, this is also what has caused the surge in the Coffee Shop business in big cities, especially in Jakarta and one of them is Jail Coffee Kemayoran. This study aims to find out that consumer preference factors play a role and also affect buying interest at Jail Coffee Kemayoran. The type of research conducted is quantitative associative, with the distribution of questionnaires carried out using the Google Form application with a total of 100 respondents. Respondent data was then processed using SPSS 25. In the study, various types of tests were carried out consisting of validity tests, reliability tests, classical assumption tests, simple linear regression tests, partial T tests, and determination coefficient tests. Based on the results of the research conducted, it was shown that consumer preference factors partially affected the buying interest at Jail Coffee Kemayoran in the hypothesis testing carried out.